Quality of Education Services in Schools - Isnawati Mohamad; I Wayan Sudana (International Conference on Science, Education, and Technology, 2021)
This paper aims to explain the quality of education services in schools referring to the principles of school governance. Using qualitative methods with secondary data, because it comes from literature data sources. The Milles&Huberman model interactively analyzed with data reduction steps, data display and conclusion drawing. The final result is known that; 1) the phenomenon at SMPN Lembang, transparency and accountability are not optimal because they are only delivered through ceremonies, not yet accompanied by access for parents and students to obtain information about the implementation of school governance; 2) there is a gap in facilities and infrastructure between MI Darul Ulum Bima, SDN 29 Jambi, SMA YASPORBI Jakarta which have an effect on differences in the efficiency of school management and have an impact on the quality of education; 3) a phenomenon in one of the Kab. Sambas who did not prepare information about the school's passive assets, so that it has the potential to be dysfunctional; 4) a phenomenon that occurs in 3 SMA and 3 SMK in DI Yogyakarta that have implemented a SIM and feel the benefits in the form of increasing access to information with speed and accuracy for the effectiveness of academic services.